Perubahan Sensitivitas Kaki pada Diabetes Melitus Tipe 2 Setelah Dilakukan Senam Kaki - Laras Sri Ningrum; Tini Wartini; Isnayati Isnayati (Journal of Telenursing (JOTING), 2020)
The study aimed was to determine the effectiveness of diabetic foot exercises on the sensitivity of the feet of patients with type 2 diabetes mellitus. The method used in this study is a descriptive research method with a case study approach. The results showed that when measuring the feet' sensitivity after doing foot exercises 2x / day for three days, there was a change. Changes in the sensitivity value increased 1-2 points from the maximum point 3. In conclusion, the implementation of foot exercises can improve the feet' sensitivity in patients with type 2 diabetes mellitus. Keywords: Type 2 Diabetes Mellitus, Foot Exercise, Foot Sensitivity